Dance Appreciation: Cultivating Empathy in the 21st Century - Farhan Apriadhi Ghazaly; Dwi Kusumawardani; Rizki Taufik Rakhman (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Entering the 21st century era, education is required to not only develop cognitive aspects, but also the character and life skills of students. One important ability that needs to be cultivated is empathy as the foundation of healthy and humanist social interaction. This article examines the role of dance appreciation in shaping students' empathy through a literature review approach. Dance appreciation is seen not only as an activity of observing performances, but also as a process of appreciating the meaning, culture, and emotions implied in dance movements. Through this process, learners not only train aesthetic sensitivity, but also develop critical thinking, communication, collaboration, and creativity (4C) skills. In addition, dance appreciation can be a safe space for self-reflection, development of social awareness, and the formation of a more empathetic character. Thus, dance has a strategic contribution in answering the challenges of 21st century education, especially in building a cultured young generation and noble personality.